An Investigating the effect of financing, market power, bank liquidity creation channel on the monetary policy of the Iranian economy - Zahmatkeshan, Javad; Sabouri, Narges (International Journal of Business Management and Entrepreneurship, 2022)
According to Dong and Hayon’s study in 2022, in order to improve monetary policy, banks may use indicators that can be used to control their monetary policy; The indicators used in this study include financing, market power, liquidity creation channel; So there is a possibility that these indicators have a role on monetary policy. In order to analyze the hypotheses of the research, the statistical population was selected from 2016 to 2021 and for 6 years and included commercial banks and financial institutions admitted to the stock exchange, and the statistical sample was selected using the elimination method and the number of 21 banks. The research method used is a descriptive-analytical method and historical research data was collected and classified by referring to financial statements and financial reports of commercial banks and financial institutions admitted to the stock exchange. The panel data method was used to analyze the statistical data; And in the analysis section, descriptive and inferential statistics and various related tests were performed and data analysis was done using Eviews version 9 software. According to the regression model analysis, the findings of the research show that bank financing, market power and the bank’s liquidity creation channel have a positive and significant effect on the monetary policy of commercial banks and financial institutions admitted to the Tehran Stock Exchange, so that in this research, based on the statistics t The degree of effectiveness of special hypotheses was determined that bank financing, liquidity creation channel, and market power affect monetary policy, respectively.